2008
DOI: 10.1007/s00394-008-0704-0
|View full text |Cite
|
Sign up to set email alerts
|

Chemoprevention by white currant is mediated by the reduction of nuclear β-catenin and NF-κB levels in Min mice adenomas

Abstract: This study shows that white currant is effective in preventing cancer initiation and progression in the Min mouse. Whether the positive effects are due to its special phenolic composition needs to be studied in more detail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…It has been shown to reduce the incidence of a variety of carcinogen-induced tumors 20 . The anticarcinogenic effect of EA was shown in several types of cancers [21][22][23][24][25] . In our study we observed, EA at 25-200µM strikingly reduced the cell viability of U251 cells, suggesting the anti-proliferative efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown to reduce the incidence of a variety of carcinogen-induced tumors 20 . The anticarcinogenic effect of EA was shown in several types of cancers [21][22][23][24][25] . In our study we observed, EA at 25-200µM strikingly reduced the cell viability of U251 cells, suggesting the anti-proliferative efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of various factors, such as iNOS, cyclooxygenase-2, etc., is associated with the upregulation of inflammatory processes that are regulated by NF-κB [23]. Colon cancer patients are reported to have high levels of active NF-κB, which stimulate tumor progression [24]. Results from the present study show that triptolide enhances PPARγ levels and reduces iNOS levels in HCT116 cells.…”
Section: Discussionmentioning
confidence: 50%
“…As assessed by microarray analyses, with berry enriched diets the authors observed attenuation of genes implicated in colon carcinogenesis, including the decreased expression of the adenosine deaminase, ecto-5′-nucleotidase, and prostaglandin E2 receptor subtype EP4, thus suggesting some mechanistic evidence as to a potential explanation for the tumor risk reduction. In separate in vivo experiments also on Min mice, Rajakangas et al, showed that a 10% white currant dietary supplementation administered for 10 weeks can yield a significant reduction in the number and size of adenomas in the total small intestine, associated with reduced nuclear beta-catenin and NF-κB protein levels in the adenomas [60]. …”
Section: The Role Of Dietary Berries In Various Types Of Cancermentioning
confidence: 99%